2023
DOI: 10.1021/acsomega.3c02084
|View full text |Cite
|
Sign up to set email alerts
|

MoS2-Based Nanocomposites for Photocatalytic Hydrogen Evolution and Carbon Dioxide Reduction

Abstract: Photocatalysis is a facile and sustainable approach for energy conversion and environmental remediation by generating solar fuels from water splitting. Due to their two-dimensional (2D) layered structure and excellent physicochemical properties, molybdenum disulfide (MoS 2 ) has been effectively utilized in photocatalytic H 2 evolution reaction (HER) and CO 2 reduction. The photocatalytic efficiency of MoS 2 greatly depends on the active edge sites present in their layered structure. Modifications like reducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 200 publications
0
3
0
Order By: Relevance
“…Molybdenum disulfide (MoS 2 ), a prominent member of the 2D transition-metal dichalcogenides (TMDCs) family and renowned for its versatile role as a catalyst of various chemical processes such as hydrotreatment of petroleum cuts or biomass conversion , has recently shown promise for various electro- and photocatalytic applications. In particular, the electrochemical hydrogen evolution reaction (HER) , and CO 2 photoreduction could be catalyzed by MoS 2 . , As an example, Asadi et al demonstrated high efficiency of MoS 2 for electrochemical reduction of CO 2 , outperforming noble metals, particularly at its Mo-terminated edges . They showcased a high current density for carbon monoxide (CO) formation at low overpotential in an ionic liquid, which was also deemed responsible for the observed suppression of the competing HER, as also shown previously .…”
Section: Introductionmentioning
confidence: 62%
“…Molybdenum disulfide (MoS 2 ), a prominent member of the 2D transition-metal dichalcogenides (TMDCs) family and renowned for its versatile role as a catalyst of various chemical processes such as hydrotreatment of petroleum cuts or biomass conversion , has recently shown promise for various electro- and photocatalytic applications. In particular, the electrochemical hydrogen evolution reaction (HER) , and CO 2 photoreduction could be catalyzed by MoS 2 . , As an example, Asadi et al demonstrated high efficiency of MoS 2 for electrochemical reduction of CO 2 , outperforming noble metals, particularly at its Mo-terminated edges . They showcased a high current density for carbon monoxide (CO) formation at low overpotential in an ionic liquid, which was also deemed responsible for the observed suppression of the competing HER, as also shown previously .…”
Section: Introductionmentioning
confidence: 62%
“…(3) Nanofibers as catalysts for the conversion and sequestration of CO 2 [99]; (4) Nanocomposites for photocatalytic CO 2 reduction and H 2 evolution reactions [100];…”
Section: Climate Change and Nano-farmingmentioning
confidence: 99%
“…Various reports have shown that SnS 2 can be utilized in numerous photocatalytic applications, such as hydrogen production, 31–34 wastewater treatment, 35–39 antibacterial and antifungal activity, 40–43 and air purification. 44 For example, Yu et al 45 first reported the photocatalytic hydrogen production of SnS 2 nanosheets under solar light simulation with H 2 evolution activity of 1.06 mmol h −1 g −1 .…”
Section: Introductionmentioning
confidence: 99%